Recyclable high barrier composite packaging film

A functional barrier agent was prepared by combining modified montmorillonite nanosheets with ethylene vinyl alcohol copolymer, which solved the problems of difficult recycling and light sensitivity of high-barrier packaging films, and achieved a high efficiency improvement in barrier and light blocking performance.

CN119078326BActive Publication Date: 2025-12-30SUZHOU ZIJIN PLASTIC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411298576.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-12-30
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Existing high-barrier packaging films face difficulties in recycling, and dairy product packaging films are sensitive to light, leading to environmental pollution and resource waste. The existing plastic packaging films have insufficient barrier properties and cannot meet actual needs.

Method used

A functional barrier agent was prepared by combining modified montmorillonite nanosheets with ethylene vinyl alcohol copolymer, and by synthesizing light-blocking coupling monomers and crosslinking monomers to modify the montmorillonite nanosheets. The composite packaging film was then prepared using an eleven-layer co-extrusion blow molding process.

Benefits of technology

It improves the barrier and light-blocking properties of the packaging film, while enhancing the interfacial compatibility and mechanical properties of the material, and achieving excellent recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119078326B_ABST
    Figure CN119078326B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of functional packaging film research and development, and discloses a recyclable high-barrier composite packaging film, which comprises the following steps: synthesizing silane monomers containing triazine ultraviolet absorption groups, phenolic hydroxyl functional groups and hydrolysis functional groups; preparing modified montmorillonite by carrying out dehydration condensation reaction between the silicon hydroxyl functional groups obtained by hydrolysis reaction of the hydrolysis functional groups of the silane monomers and the hydroxyl functional groups possessed by sodium-based montmorillonite; preparing a composite barrier agent by carrying out hydrogen bonding between the phenolic hydroxyl functional groups possessed by the silane monomers in the modified montmorillonite and the hydroxyl functional groups contained in ethylene-vinyl alcohol copolymer, and compounding the modified montmorillonite and the ethylene-vinyl alcohol copolymer; and preparing a recyclable high-barrier composite packaging film with excellent barrier performance by adopting an eleven-layer co-extrusion blow molding film process with polyethylene resin as a single raw material and the composite barrier agent as a modification reagent, which can be applied in the field of dairy product packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional packaging film research and development technology, specifically to a recyclable high-barrier composite packaging film. Background Technology

[0002] Packaging films protect products from moisture absorption, oxidation, and other deterioration, and are widely used in the food, pharmaceutical, and cosmetic industries. For most food packaging films, water and oxygen barrier properties are crucial for evaluating their performance, especially for products susceptible to moisture and oxidation, such as milk powder, cheese, and yogurt. Currently, high-barrier packaging films on the market often use aluminum foil as the water and oxygen barrier layer, featuring a multi-layered composite structure of outer protective layer / adhesive / aluminum foil / adhesive / heat-sealing layer. However, while aluminum foil packaging films offer excellent water and oxygen barrier properties, recycling is extremely difficult. Post-use sorting and classification are cumbersome and challenging, resulting in low recycling rates. Improper disposal and indiscriminate dumping can lead to serious environmental pollution and resource waste.

[0003] Single-material plastic packaging films do not require sorting during recycling and can be reused, but their barrier properties often fail to meet practical application requirements. Currently, the main methods to improve the barrier properties of plastic packaging films include composite inorganic nanosheet materials (graphene nanosheets, montmorillonite nanosheets, cellulose nanocrystals, etc.) and co-extrusion using high-barrier resins (ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyvinyl chloride, etc.).

[0004] Furthermore, studies have shown that light exposure promotes the oxidative degradation of vitamin C in dairy products, making the light-blocking properties of dairy product composite packaging films crucial. Further research revealed that triazine compounds are common ultraviolet absorbers, capable of inhibiting light exposure and effectively protecting food and materials from UV damage. Summary of the Invention

[0005] This invention uses montmorillonite nanosheets, an inorganic raw material with excellent barrier properties, and ethylene-vinyl alcohol copolymer, an organic raw material, as barrier modification materials. To improve the interfacial compatibility and interfacial interaction between montmorillonite nanosheets and ethylene-vinyl alcohol copolymer, this invention develops a novel light-blocking coupling monomer and a light-blocking crosslinking monomer. The surface of montmorillonite nanosheets is modified using the light-blocking coupling monomer and / or the light-blocking crosslinking monomer, and then compounded with ethylene-vinyl alcohol copolymer to obtain a functional barrier agent. Introducing the functional barrier agent into a single PE material, since the modified montmorillonite nanosheets can be more uniformly dispersed when compounded with ethylene-vinyl alcohol copolymer, the technical goal of synergistically improving the barrier performance of packaging materials is achieved.

[0006] A method for preparing a recyclable high-barrier composite packaging film includes the following steps:

[0007] Step 1: Synthesize a silane monomer containing a triazine UV-absorbing group, a phenolic hydroxyl functional group, and a hydrolysis functional group. This silane monomer is a coupling monomer, and its chemical structural formula is as follows:

[0008]

[0009] Step 2: The silane monomer prepared in Step 1 undergoes a hydrolysis reaction to obtain a silanol functional group. This silanol functional group then undergoes a dehydration condensation reaction with the hydroxyl functional group on sodium-based montmorillonite to prepare modified montmorillonite.

[0010] Step 3: By using the hydrogen bonding between the phenolic hydroxyl functional groups of the silane monomer in the modified montmorillonite prepared in Step 2 and the hydroxyl functional groups in the ethylene-vinyl alcohol copolymer, the modified montmorillonite and the ethylene-vinyl alcohol copolymer are combined to prepare a composite barrier agent.

[0011] Step 4: Using polyethylene resin as a single raw material and composite barrier agent as a modifying agent, design the membrane structure, formulation and dosage of each layer of the eleven-layer co-extruded film, and use the eleven-layer co-extrusion blow molding process to prepare a recyclable high-barrier composite packaging film.

[0012] Preferably, the silane monomer in step one further includes a crosslinking monomer with the following chemical structural formula:

[0013]

[0014] Preferably, the preparation method of the coupling monomer is as follows:

[0015] Step S3-1: Under Lewis acid catalysis, 1 molar equivalent of cyanuric chloride and 2.05-2.1 molar equivalents of resorcinol undergo Friedel-Crafts alkylation reaction to generate monochlorotriazine monomer;

[0016] Step S3-2: Using 3-aminopropyltrimethoxysilane as a nucleophile, a nucleophilic substitution reaction is carried out between 1 molar equivalent of monochlorotriazine monomer and 1.01-1.05 molar equivalents of 3-aminopropyltrimethoxysilane to prepare the coupling monomer.

[0017] Preferably, the method for preparing the crosslinking monomer is as follows:

[0018] Step S4-1: Under Lewis acid catalysis, 1.01-1.05 molar equivalents of cyanuric chloride and 1 molar equivalent of resorcinol undergo Friedel-Crafts alkylation reaction to generate dichlorotriazine monomer;

[0019] Step S4-2: Using 3-aminopropyltrimethoxysilane as a nucleophile, a crosslinking monomer is prepared by nucleophilic substitution reaction between 1 molar equivalent of dichlorotriazine monomer and 2.01-2.05 molar equivalents of the amino functional group of 3-aminopropyltrimethoxysilane.

[0020] Preferably, the Lewis acid catalyst is one of aluminum trichloride, ferric trichloride, tin tetrachloride, and zinc dichloride.

[0021] Preferably, the formulation and dosage of the recyclable high-barrier composite packaging film are as follows:

[0022] First layer: The formulation is 20-80 wt% LDPE + 20-80 wt% LLDPE, and the dosage is 5-15 wt%.

[0023] Second layer: The formulation is 40-80 wt% HDPE + 20-60 wt% m-LLDPE, and the dosage is 3-10 wt%;

[0024] The third layer: The formulation is 20-60 wt% LDPE + 40-80 wt% m-LLDPE, and the dosage is 5-15 wt%.

[0025] Fourth layer: The formula is 100wt% PE-g-MAH, and the dosage is 1-5wt%.

[0026] Fifth layer: The formula is 95-99 wt% LDPE + 1-5 wt% EVOH, and the dosage is 5-15 wt%.

[0027] The sixth layer consists of 90-99 wt% LDPE + 1-10 wt% composite barrier agent, with a dosage of 10-40 wt%.

[0028] The composite barrier agent is formulated with sodium montmorillonite, silane monomer, and ethylene-vinyl alcohol copolymer in a mass ratio of 1:(0.5-3):(1-10).

[0029] Seventh layer: The formula is 95-99 wt% LDPE + 1-5 wt% EVOH, and the dosage is 5-15 wt%.

[0030] Eighth layer: The formula is 100wt% PE-g-MAH, and the dosage is 1-5wt%.

[0031] Ninth layer: The formula is 20-60 wt% LDPE + 40-80 wt% m-LLDPE, and the dosage is 5-15 wt%.

[0032] Tenth layer: The formula is 40-80 wt% HDPE + 20-60 wt% m-LLDPE, and the dosage is 3-10 wt%.

[0033] Eleventh layer: The formula is 20-80 wt% LDPE + 20-80 wt% LLDPE, and the dosage is 5-15 wt%.

[0034] Preferably, the sodium-based montmorillonite powder has a sheet diameter of 15 μm and a thickness of 13 nm.

[0035] The water vapor transmission rate of the recyclable high-barrier composite packaging film prepared according to the above method is 0.5–1.5 g / (m²). 2 ·24h)], oxygen permeability is 0.5~1.5 [cm] 3 / (m 2 ·24h·0.1MPa)).

[0036] The application of a recyclable high-barrier composite packaging film prepared according to the above method in the field of dairy product packaging.

[0037] Beneficial effects:

[0038] This invention first synthesizes light-blocking coupling monomers and light-blocking crosslinking monomers. The inorganic raw material montmorillonite nanosheets are surface modified using light-blocking coupling monomers and / or light-blocking crosslinking monomers with ultraviolet absorption function. Then, they are compounded with organic ethylene vinyl alcohol copolymers to obtain a functional barrier agent. The functional barrier agent is introduced into a single PE material and a composite packaging film is prepared by using an eleven-layer co-extrusion blow molding process.

[0039] This technique enhances the interfacial compatibility between montmorillonite and the ethylene-vinyl alcohol copolymer matrix, and also improves the light-blocking properties of the polymer material.

[0040] Experimental results show that the composite packaging film prepared by this invention not only has excellent barrier properties, but also excellent light blocking properties. Attached Figure Description

[0041] Figure 1 These are the performance test results of the composite packaging film. Detailed Implementation

[0042] Experimental Example 1:

[0043] The synthetic route for preparing light-blocking coupling monomers is as follows:

[0044]

[0045] The preparation steps of the light-blocking coupling monomer are as follows:

[0046] Step 1: Under the catalysis of Lewis acid, 1 molar equivalent of cyanuric chloride and 2.05-2.1 molar equivalents of resorcinol undergo a Friedel-Crafts alkylation reaction to generate a monochlorotriazine monomer;

[0047] Among them, Lewis acid is selected from one of aluminum trichloride, ferric trichloride, tin tetrachloride, and zinc dichloride; aluminum trichloride is selected in this experimental example.

[0048] Step 2: Using 3-aminopropyltrimethoxysilane as a nucleophile, a nucleophilic substitution reaction is carried out between 1 molar equivalent of monochlorotriazine monomer and 1.01-1.05 molar equivalent of 3-aminopropyltrimethoxysilane to generate a light-blocking coupling monomer.

[0049] The specific experimental steps for light-blocking coupling monomers are as follows:

[0050] 1.8 g of cyanuric chloride, 1.5 g of anhydrous aluminum trichloride, 2.3 g of resorcinol and 50 mL of chlorobenzene were added to a four-necked flask, heated to 80 °C and stirred for 3 h. After cooling, an ice-water mixture was added, and the mixture was heated under reflux to separate the chlorobenzene. The mixture was then filtered, washed with deionized water, and dried to obtain the monochlorotriazine monomer.

[0051] 1.6 g of monochlorotriazine monomer and 30 mL of N,N-dimethylformamide were added to a three-necked flask and stirred at room temperature until completely dissolved. Then, 10 mL of 3-aminopropyltrimethoxysilane solution (prepared from 0.9 g of 3-aminopropyltrimethoxysilane and 10 mL of N,N-dimethylformamide) and 1.3 mL of triethylamine were added to the three-necked flask. The mixture was heated to 40 °C and stirred for 5 h. After filtration, the mixture was washed successively with deionized water and ethanol and dried to obtain the light-blocking coupling monomer.

[0052] The 1H NMR characterization of the light-blocking coupling monomer is as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.72-0.76 (t, 2H), 1.91-1.98 (m, 2H), 3.27-3.31 (t, 2H), 3.63 (s, 9H), 6.61-6.66 (m, 4H), 7.97-7.99 (d, 2H).

[0053] Experimental Example 2:

[0054] The synthetic route for preparing the light-blocking crosslinking monomer is as follows:

[0055]

[0056] The preparation steps of the light-blocking crosslinking monomer are as follows:

[0057] Step 1: Under the catalysis of Lewis acid, 1.01-1.05 molar equivalents of cyanuric chloride and 1 molar equivalent of resorcinol undergo a Friedel-Crafts alkylation reaction to generate a dichlorotriazine monomer;

[0058] Among them, Lewis acid is selected from one of aluminum trichloride, ferric trichloride, tin tetrachloride, and zinc dichloride; aluminum trichloride is selected in this experimental example.

[0059] Step 2: Using 3-aminopropyltrimethoxysilane as a nucleophile, a nucleophilic substitution reaction is carried out between 1 molar equivalent of dichlorotriazine monomer and 2.01-2.05 molar equivalents of the amino functional group of 3-aminopropyltrimethoxysilane to generate a light-blocking crosslinking monomer.

[0060] The specific experimental steps for light-blocking crosslinking monomers are as follows:

[0061] 1.9 g of cyanuric chloride, 0.9 g of anhydrous aluminum trichloride, 1.1 g of resorcinol and 50 mL of chlorobenzene were added to a four-necked flask, heated to 80 °C and stirred for 3 h. After cooling, an ice-water mixture was added, and the mixture was heated under reflux to separate the chlorobenzene. The mixture was then filtered, washed with deionized water, and dried to obtain the dichlorotriazine monomer.

[0062] 1.3 g of dichlorotriazine monomer and 30 mL of N,N-dimethylformamide were added to a three-necked flask and stirred at room temperature until completely dissolved. Then, 10 mL of 3-aminopropyltrimethoxysilane solution (prepared from 1.9 g of 3-aminopropyltrimethoxysilane and 10 mL of N,N-dimethylformamide) and 1.7 mL of triethylamine were added to the three-necked flask in sequence. The mixture was heated to 40 °C and stirred for 5 h. After filtration, the mixture was washed successively with deionized water and ethanol and dried to obtain a light-blocking crosslinking monomer.

[0063] The 1H NMR characterization of the light-blocking crosslinked monomer is as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.72-0.76 (t, 4H), 1.91-1.98 (m, 4H), 3.26-3.29 (t, 4H), 3.63 (s, 18H), 6.53-6.62 (m, 2H), 7.97-7.99 (d, 1H).

[0064] Example 1:

[0065] (1) Preparation of light-blocking modified montmorillonite I: The preparation method is as follows: montmorillonite nanosheets (montmorillonite nanosheets contain hydroxyl groups on their surface) are modified with light-blocking coupling monomers to obtain light-blocking modified montmorillonite I.

[0066] The mechanism by which the light-blocking coupling monomer modifies montmorillonite nanosheets is as follows: the hydrolytic functional group of the light-blocking coupling monomer undergoes a hydrolysis reaction to generate a silanol functional group, which then undergoes a condensation reaction with the hydroxyl functional group on the surface of the montmorillonite nanosheets.

[0067] The specific experimental steps for light-blocking modified montmorillonite I are as follows: 2g of sodium-based montmorillonite powder, 80mL of anhydrous ethanol and 20mL of deionized water are added to a beaker, ultrasonically treated for 10min, heated to 40℃, and then 3g of light-blocking coupling monomer and 2 drops of glacial acetic acid are added to the beaker in sequence. The mixture is stirred and reacted at 40℃ for 10h, centrifuged, and washed repeatedly by centrifugation with anhydrous ethanol and deionized water in sequence. After vacuum drying, light-blocking modified montmorillonite I is obtained.

[0068] The preparation method of functional barrier agent I is as follows: the phenolic hydroxyl functional group of the light-blocking coupling monomer in the light-blocking modified montmorillonite I undergoes hydrogen bonding with the hydroxyl functional group contained in the ethylene-vinyl alcohol copolymer, thereby achieving effective composite of montmorillonite and ethylene-vinyl alcohol copolymer, and thus preparing functional barrier agent I.

[0069] The specific experimental steps for functional barrier agent I are as follows: 15g of ethylene-vinyl alcohol copolymer and 5g of light-blocking modified montmorillonite I are added to a twin-screw extruder, and the functional barrier agent I is prepared by blending, melting, extruding and pelletizing through a twin-screw extruder;

[0070] (2) Preparation of light-blocking modified montmorillonite II: The preparation method is as follows: montmorillonite nanosheets (containing hydroxyl groups on the surface of montmorillonite nanosheets) are modified by using light-blocking coupling monomers and light-blocking crosslinking monomers to obtain light-blocking modified montmorillonite II.

[0071] The mechanism by which the light-blocking coupling monomer and the light-blocking crosslinking monomer jointly modify montmorillonite nanosheets is as follows: the hydrolytic functional groups of the light-blocking coupling monomer and the light-blocking crosslinking monomer undergo a hydrolysis reaction to generate silanol functional groups, which then undergo a condensation reaction with the hydroxyl functional groups on the surface of the montmorillonite nanosheets.

[0072] The specific experimental steps for light-blocking modified montmorillonite II are the same as those for the preparation of light-blocking modified montmorillonite I. The only difference is that 3g of light-blocking coupling monomer is replaced with 1.5g of light-blocking coupling monomer and 1.5g of light-blocking crosslinking monomer.

[0073] The preparation method of functional barrier agent II is as follows: the phenolic hydroxyl functional groups of the light-blocking coupling monomer and the light-blocking crosslinking monomer in the light-blocking modified montmorillonite II undergo hydrogen bonding with the hydroxyl functional groups contained in the ethylene-vinyl alcohol copolymer, thereby achieving effective composite of montmorillonite and ethylene-vinyl alcohol copolymer, and thus preparing functional barrier agent II.

[0074] The specific experimental steps for functional barrier agent II are the same as those for the preparation of functional barrier agent I, with the only difference being that light-blocking modified montmorillonite I is replaced with light-blocking modified montmorillonite II.

[0075] (3) Preparation of blended barrier agent: Montmorillonite nanosheets are directly dispersed in ethylene-vinyl alcohol copolymer matrix to prepare blended barrier agent. The specific experimental steps are the same as the preparation experiment of functional barrier agent I. The only difference is that sodium-based montmorillonite powder is used to replace light-blocking modified montmorillonite I.

[0076] Example 2:

[0077] (1) Preparation of composite packaging film I, including the following steps:

[0078] Step 1: Set up composite packaging film I as an eleven-layer symmetrical film structure. The formulation and dosage of each layer are as follows:

[0079] First layer: The formula is 50wt% LDPE + 50wt% LLDPE, and the amount used is 10wt%;

[0080] Second layer: The formula is 60wt% HDPE + 40wt% m-LLDPE, and the dosage is 5wt%;

[0081] The third layer: The formulation is 40wt% LDPE + 60wt% m-LLDPE, and the dosage is 10wt%;

[0082] Fourth layer: The formula is 100wt% PE-g-MAH, and the dosage is 2.5wt%;

[0083] Fifth layer: The formula is 98wt% LDPE + 2wt% EVOH, and the dosage is 10wt%.

[0084] Sixth layer: The formula is 95wt% LDPE + 5wt% functional barrier agent I, with a dosage of 25wt%;

[0085] Seventh layer: The formula is 98wt% LDPE + 2wt% EVOH, and the dosage is 10wt%.

[0086] Eighth layer: The formula is 100wt% PE-g-MAH, and the dosage is 2.5wt%;

[0087] Ninth layer: 40wt% LDPE + 60wt% m-LLDPE, 10wt% in amount;

[0088] Tenth layer: The formula is 60wt% HDPE + 40wt% m-LLDPE, and the dosage is 5wt%.

[0089] Eleventh layer: The formula is 50wt% LDPE + 50wt% LLDPE, and the dosage is 10wt%.

[0090] Step 2: The raw materials from Step 1 are fed into the hoppers of the eleven screw extruders of the eleven-layer co-extrusion film blow molding unit. After mixing, the molten resin is collected at the die head through the distributor, extruded through the die head, blow molded, cooled, and wound up to obtain a composite packaging film I with a thickness of 80μm.

[0091] The process parameters for the screw extruders corresponding to the first, second, third, ninth, tenth, and eleventh layers are set as follows: the temperatures of zones 1-3 are 120℃, 150℃, and 170℃, respectively; the runner temperature is 165℃; and the rotation speed is 30r / min.

[0092] The process parameters for the screw extruders corresponding to the fourth and eighth layers are set as follows: the temperatures of zones 1-3 are 125℃, 150℃, and 165℃, respectively; the runner temperature is 160℃; and the rotation speed is 15r / min.

[0093] The process parameters for the screw extruders corresponding to the fifth, sixth, and seventh layers are set as follows: the temperatures of zones 1-3 are 140℃, 160℃, and 180℃, respectively; the runner temperature is 175℃; and the rotation speed is 40r / min.

[0094] (2) Preparation of composite packaging film II: Only functional barrier agent II is used to replace functional barrier agent I in composite packaging film I, and the rest are the same as composite packaging film I, to prepare composite packaging film II.

[0095] (3) Preparation of composite packaging film a: Only the blended barrier agent is used to replace the functional barrier agent I in composite packaging film I, and the rest are the same as composite packaging film I. The composite packaging film is prepared and used as comparative example 1.

[0096] (4) Preparation of composite packaging film b: Only ethylene-vinyl alcohol copolymer is used to replace the functional barrier agent I in composite packaging film I, and the rest are the same as composite packaging film I. Composite packaging film b is prepared and used as comparative example 2.

[0097] The specifications and manufacturers of the raw materials used in the specific implementation are shown in Table 1.

[0098] Table 1 Experimental Materials

[0099]

[0100] Performance testing:

[0101] (1) Barrier performance: The barrier performance of the samples was tested using a Y110 oxygen transmission rate tester and a TC-03 water vapor transmission rate tester in accordance with GB / T 1038-2000 and GB / T 1037-2021, respectively.

[0102] (2) Light blocking performance: The transmittance of the sample was tested using a Lambda 950 UV-Vis spectrophotometer in accordance with GB / T2410-2008. The test wavelength range was 250-800nm, and the transmittance of the sample at 380nm was recorded.

[0103] (3) Mechanical properties: The 30mm×5mm sample was fixed on the Instron 5565 universal tensile testing machine and tensile test was performed at a tensile rate of 5mm / min. The longitudinal and transverse tensile strengths were recorded respectively.

[0104] The experimental results are shown in Table 2 below. Figure 1 .

[0105] Table 2. Performance test results of composite packaging film

[0106]

[0107]

[0108] A comprehensive analysis of the above experimental results leads to the following conclusions:

[0109] (1) The barrier agent obtained by modifying montmorillonite nanosheets with light-blocking coupling monomers and / or light-blocking crosslinking monomers and then compounding them with ethylene vinyl alcohol copolymer has a very significant effect on improving the barrier performance of composite packaging film.

[0110] Among them, the barrier agent obtained by synergistic modification of montmorillonite nanosheets with light-blocking coupling monomers and light-blocking crosslinking monomers and then compounding them with ethylene vinyl alcohol copolymer has the best effect on improving the barrier performance of composite packaging film.

[0111] (2) This invention not only endows the composite packaging film with excellent light blocking ability, but also improves the overall mechanical properties of the material.

Claims

1. A method for preparing a recyclable high barrier composite packaging film, characterized by, The method comprises the following steps: Step 1: a hydrolysis reaction occurs through the hydrolysis of functional groups of silane monomers to obtain silicon hydroxyl functional groups, and a dehydration condensation reaction occurs between the silicon hydroxyl functional groups and hydroxyl functional groups carried by sodium-based montmorillonite, so as to prepare modified montmorillonite; wherein the silane monomers are light-blocking coupling monomers and light-blocking crosslinking monomers; The chemical structure of the light-blocking coupling monomers is as follows: ; The chemical structure of the light-blocking crosslinking monomers is as follows: ; Step 2: the modified montmorillonite is compounded with ethylene-vinyl alcohol copolymer through hydrogen bonding between phenolic hydroxyl functional groups carried by the silane monomers in the modified montmorillonite and hydroxyl functional groups contained in the ethylene-vinyl alcohol copolymer, so as to prepare a composite barrier agent; The mass ratio of sodium-based montmorillonite, light-blocking coupling monomers, light-blocking crosslinking monomers and ethylene-vinyl alcohol copolymer in the composite barrier agent is 1:0.75:0.75:7.5; Step 3: a recyclable high-barrier composite packaging film is prepared by using a 11-layer co-extrusion blow molding process, with polyethylene resin as a single raw material and the composite barrier agent as a modification reagent, and the film structure, the formulation and the amount of each film layer of the 11-layer co-extrusion film being designed.

2. A process for the preparation of a recyclable high barrier composite packaging film as claimed in claim 1, wherein, The preparation method of the light-blocking crosslinking monomers is as follows: Step S2-1: 1.01-1.05 molar equivalents of cyanuric chloride react with 1 molar equivalent of resorcinol under the catalysis of a Lewis acid to generate dichlorotriazine monomers through Friedel-Crafts alkylation; Step S2-2: the light-blocking crosslinking monomers are prepared by nucleophilic substitution reaction between 1 molar equivalent of the dichlorotriazine monomers and 2.01-2.05 molar equivalents of amino functional groups of 3-aminopropyltrimethoxysilane, with 3-aminopropyltrimethoxysilane as a nucleophilic reagent.

3. The method of claim 2, wherein the method further comprises the step of adding a barrier layer to the outer surface of the first polymeric layer. The Lewis acid catalyst is one of aluminum trichloride, iron trichloride, tin tetrachloride and zinc dichloride.

4. The method of claim 1, wherein the method further comprises the step of adding a barrier layer to the outer surface of the first polymeric layer. The formulation and amount of the recyclable high-barrier composite packaging film are as follows: The first layer: the formulation is 20-80wt% LDPE+20-80wt% LLDPE, and the amount is 5-15wt%; The second layer: the formulation is 40-80wt% HDPE+20-60wt% m-LLDPE, and the amount is 3-10wt%; The third layer: the formulation is 20-60wt% LDPE+40-80wt% m-LLDPE, and the amount is 5-15wt%; The fourth layer: the formulation is 100wt% PE-g-MAH, and the amount is 1-5wt%; The fifth layer: the formulation is 95-99wt% LDPE+1-5wt% EVOH, and the amount is 5-15wt%; The sixth layer: the formulation is 90-99wt% LDPE+1-10wt% composite barrier agent, and the amount is 10-40wt%; The seventh layer: the formulation is 95-99wt% LDPE+1-5wt% EVOH, and the amount is 5-15wt%; The eighth layer: the formulation is 100wt% PE-g-MAH, and the amount is 1-5wt%; The ninth layer: the formulation is 20-60wt% LDPE+40-80wt% m-LLDPE, and the amount is 5-15wt%; The tenth layer: the formula is 40-80wt% HDPE+20-60wt% m-LLDPE, the dosage is 3-10wt%; The eleventh layer: the formula is 20-80wt% LDPE+20-80wt% LLDPE, the dosage is 5-15wt%.

5. The method for preparing a recyclable high-barrier composite packaging film according to claim 1, characterized in that, The sodium-based montmorillonite has a flake diameter of 1-5μm and a thickness of 1-3nm.

6. A recyclable high barrier composite packaging film prepared according to the method of any one of claims 1-5, characterized in that, The composite packaging film has a water vapor transmission rate of 0.5-1.0 [g / (m 2 •24h)] and an oxygen transmission rate of 0.5-1.0 [cm 3 / (m 2 •24h•0.1 MPa)].

7. The use of the recyclable high-barrier composite packaging film according to claim 6 in the field of dairy product packaging.

Citation Information

Patent Citations

  • Mildew-proof and antibacterial plastic, preparation method thereof and application of mildew-proof and antibacterial plastic in tooth glass

    CN118256055A

  • Preparation method and application of eleven-layer co-extruded high-barrier high-strength recyclable liquid packaging material

    CN118578745A